(untitled) (Research, Society and Development, 2022)
The aim of this work was to investigate the dual use of veterinary laboratories in carrying out human tests during the COVID-19 pandemic in Brazil in 2020. The methodology adopted used bibliographic research techniques, of an applied nature, descriptive type, through exploratory reading and general and in-depth review of the theme. The use of veterinary laboratory services represented 9.58% of the laboratories that performed RT-qPCR COVID-19 tests, with 3.34% of tests performed and an average of 3,072 tests, being one of the lowest averages of the registered laboratories. The article highlights the relevance and potential of dual use of veterinary laboratories for the security of the country in the face of health crises, collaborating with the diagnosis of COVID-19. During the pandemic, it became clear that there is a need for greater mobilization of veterinary laboratories and human resources. Other veterinary laboratories may be available in the future and make their structure, equipment and technical personnel available to contribute to health services in Brazil. It is important to develop a security policy and a strategy of national security, with an improvement in the capacity to respond more efficiently in cases of confrontation of new epidemics and pandemics. Therefore, it is concluded that despite few laboratories have been used, the use of veterinary laboratories is of great relevance, especially in situations when there is an extraordinary increase in the demand for diagnostic tests of human samples in the health service.